Digital literacy scale of English pre-service teachers and their perceived readiness toward the application of digital technologies - Khaira Liza; Erna Andriyanti (Journal of Education and Learning (EduLearn), 2020)
High digital literacy is significantly needed by English teachers in the trend of industrial revolution 4.0 to promote a better quality of English teaching and learning. However, a significant number of English teachers, as well as pre-service teachers, still had low digital literacy scale and they were not ready to implement digital technologies into English teaching and learning process. This study was aimed to describe the digital literacy scale of graduate school students of English Education Department in a state university in Yogyakarta as pre-service teachers and their readiness toward the application of digital technologies in teaching and learning contexts. The research used mix-methods to collect both quantitative and qualitative data through Likert-scale questionnaires and interviews. The study revealed that the research participants had high digital literacy scales and readiness toward the application of digital technologies. Thus, those graduate school students as pre-service teachers could fulfill the requirements of professional English teachers in terms of digital literacy and improve the quality of English teaching and learning output by integrating digital technologies.